EXPLORING TEACHERS’ EXPERIENCES IN IMPLEMENTING DIGITAL FORMATIVE ASSESSMENT IN TECHNOLOGY-ENHANCED CLASSROOMS - Wayan Maba; Ida Bagus Nyoman Mantra; Ida Ayu Made Sri Widiastuti (International Journal of Multidisciplinary Reseach, 2026)
The rapid development of digital technology has altered the way formative assessment is implemented in English language education by allowing teachers to track learning progress, deliver instant feedback and promote student-centred instruction. The objective of this study is to investigate the experiences of English teachers in adopting digital formative assessment in technology-enhanced classrooms. A qualitative multiple case study design was adopted to explore in depth teachers' perceptions, instructional practices, problems and adaptive strategies. The study involved five purposively selected English teachers from secondary schools who had experience in incorporating digital technology into formative assessment. Data were gathered from semi-structured interviews, non-participant classroom observation and document analysis. Results showed that digital formative assessment helped teachers to deliver timely and meaningful feedback, continuously monitor students' progress, improve classroom engagement and make data-based instructional decisions. Teachers used various digital platforms and AI-assisted technologies to enhance formative assessment activities. However, the participants faced problems such as unreliable internet access, different digital skills of students, longer preparation time and worries about academic integrity. Teachers met these problems by blending several digital platforms, using authentic assessment activities, encouraging collaborative learning, and using assessment data for continual reflection to improve instruction